Lithological discrimination and mineralogical mapping using ASTER remote sensing data in the east-central Jebilet region, Morocco - El Khounaijri, Hayat; Algouti, Ahmed; Algouti, Abdellah; Essemani, Mohamed; Hadach, Fatiha; Baid, Soukaina; Ezzahzi, Salma; Kabili, Salma; Agli, Saloua; Jdaba, Naji (Geologos, 2025)
This study evaluates the effectiveness of ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) satellite data for lithological discrimination and mineralogical mapping in the east-central Jebilet region, Morocco. ASTER data offer considerable potential for detecting spectral signatures of mineral zones and determining their composition. The main objective is to apply image processing techniques, such as band ratios (BR), principal component analysis (PCA) and minimum noise fraction (MNF), in order to identify and map characteristic minerals in the region. The application of various band ratios effectively mapped the distribution of key minerals and alteration zones in the study area. The band ratio (band7/band5) was used to identify kaolinite, while the ratio (band4+band6)/band5 highlighted the presence of a mineral group constisting of alunite, kaolinite and pyrophyllite. The ratio (band7+band9)/band8 revealed a set of a carbonate mineral, chlorite and epidote, whereas endoskarns composed of epidote, chlorite and amphibole were mapped using the ratio (band6+band9)/(band7+band8). The ratio (band5+band7)/band6 characterised phyllic alteration by detecting phyllosilicate minerals such as sericite, muscovite or illite. Phengite was mapped using the band5/band6 ratio. The distribution of these minerals was closely linked to the lithological variability of previously mapped geological units, highlighting the relevance and effectiveness of band ratios for geological mapping using remote sensing. The PCA and MNF components with the highest eigenvalues significantly improved lithological discrimination by reducing noise and refining the delineation of mineral zones. The results obtained have enabled the creation of a detailed map of mineral distribution, highlighting the alteration zones and lithological formations in the eastern Jebilet region of Morocco.time-consuming, yet inexpensive method that can be applied to other areas, especially those that are difficult to reach.